If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 5y = 14 Solving -1x + 5y = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -1x + 5y + -5y = 14 + -5y Combine like terms: 5y + -5y = 0 -1x + 0 = 14 + -5y -1x = 14 + -5y Divide each side by '-1'. x = -14 + 5y Simplifying x = -14 + 5y
| 12x/1=25 | | 6*2=7x+11 | | (4x+3)=(2x-7) | | 7(z-4)+7z-3= | | [(-2)+a]-2=-7 | | 75+20h=155 | | 7x/15-1=12 | | b*(-7)*(-4)=6 | | x/2+6=8 | | bx(-7)x(-4)=6 | | 14/2+3(5)= | | -16X^2+64X+512=0 | | 19=18-A | | y^3-36y+8(y+6)= | | y^3-28y+48= | | 4z+3=47 | | y-15=-15 | | B=9(3.14)f | | -x2/10+9x/10+11/5 | | (6g*x)(6g+3h)=36g^2-9h^2 | | -1/3(6h+15) | | (x-1)/(x^2+2x-3) | | -6/x^3*-2/x^3 | | (x+2)(x+2)=2x^2+2x-11 | | 19e-27e+36=76 | | 29+58= | | 3p+5q=-14 | | 5t-u+v=3 | | x^3-9x^2+3=0 | | 6/x-2/(x+3) | | -2(x+5)-7= | | x^2-4+5x=0 |